[tex]1)\; a^7*a^{-5}=a^{7-5}=a^2\\\\2)\; \; a^{-10}:a^{-13}=a^{-10-(-13)}=a^{-10+13}=a^3\\\\3)\;(a^9)^{-2}*a^{20}=a^{-18+20}=a^2\\\\4)\; 0,8a^{11}b^{-14}*1,2a^{-8}b^{16}=0,96a^{11-8}b^{-14+16}=0,96a^3b^2[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
[tex]1)\; a^7*a^{-5}=a^{7-5}=a^2\\\\2)\; \; a^{-10}:a^{-13}=a^{-10-(-13)}=a^{-10+13}=a^3\\\\3)\;(a^9)^{-2}*a^{20}=a^{-18+20}=a^2\\\\4)\; 0,8a^{11}b^{-14}*1,2a^{-8}b^{16}=0,96a^{11-8}b^{-14+16}=0,96a^3b^2[/tex]